(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this paper, we discuss an algebraic system introduced in 2015 by Mohammed and Abdul Wahab called it a Special kind of non associative seminear-ring with BCK Algebra (SNAK-seminear ring ) where we prove some properties and give some examples . We define three types of it we, call the first is an ideal of type one, the second is an ideal of type two and the third is an ideal of type three. We prove some of properties and give some example